Environmental Law Within the Framework of European Courts and UN Charters - Bahil Jadaan, Jyan; Abbas Hasan, Qayssar (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Access to justice is the concrete means of asserting everyone's right to respect for provisions protecting the environment. Does the European Union have vocation to guarantee effective judicial protection? This article presents a difference in treatment by Union law of access to national judges and access to his own court. Indeed, if access to national judges in litigation environmental rights, is widely promoted by Union law the access to Court of Justice is, on the contrary, rigorously framed in the law of the Union and in despite proposals and demands, no substantial development can be in the area of the environment.